Carlos Manuel Varela and the Role of Memory in Covert Resistance - Puga, Ana Elena (Latin American Theatre Review, 2003)
This essay analyzes the use of memory as covert resistance to political repression in two dramas by the Uruguayan playwright Carlos Manuel Varela: Alfonso y Clotilde (1980) and Interrogatorio en Elsinore (1983). Written during Uruguay’s period of dictatorship, 1973-84, the dramas suggest several ways in which memory may be employed in the service of resistance: 1) as a covert weapon in a struggle to create an alternative reality 2) as a spur to action 3) as a guide to ethical behavior and 4) as a performance that encodes, repeats, and reinvigorates the alternative reality. The theoretical work of Pierre Nora, Michel de Certeau, and Joseph Roach help us understand theatre such as Varela’s as a site of memory, in which communal history is formed by the interplay between performers and spectators. (AEP)